Nombres comunes de las aves de Costa Rica: significado y origen - Sandoval, Luis (2006)
This paper is a compilation of the common name of the Costa Rican birds. Also are including a name explanation as the origin and uses places. Update list would permit a better communication among ornithologist and common people in conservation works.